Implementation of Mind Mapping in Social Studies Subjects on Socio-Cultural Changes for Junior High School Students - Armawati Hidayati; Faridatul Lailiyah; Ana Hidayati (Journal of Social Studies Education and Humanities Research, 2024)
The purpose of this research is to: (1) Describe the implementation of the mind mapping method, and (2) Describe the improvement of activities and learning outcomes in Social Studies (IPS). This research adopts a classroom action research (CAR) design. Based on the results of the classroom action research aimed at improving the process and learning outcomes of students, the following conclusions can be drawn: (1) The implementation of the mind mapping method in Social Studies for Grade IX students at SMPN 7 Bojonegoro involves several stages: (a) Ensure that the main theme is placed in the middle, (b) From the main theme, determine the main branches that are still related to the main theme, (c) Determine sub-topics as "branches" derived from the main branches, (d) Creatively use images, symbols, codes, and dimensions in your mind map, (e) Use lines to connect the Central Topic with the Main Topic and Sub-Topics, and (f) Develop the Mind Map according to your style. (2) The implementation of the mind mapping learning method for Grade IX students at SMPN 7 Bojonegoro in the academic year 2023/2024 can enhance their activities and learning outcomes